Stem girdling affects the quantity of CO2 transported in xylem as well as CO2 efflux from soil. Issue 3 (1st November 2013) - Bloemen, Jasper; Agneessens, Laura; Van, Lieven; Aubrey, Doug P.; McGuire, Mary Anne; Teskey, Robert O.; Steppe, Kathy
Summary There is recent clear evidence that an important fraction of root‐respired CO2 is transported upward in the transpiration stream in tree stems rather than fluxing to the soil. In this study, we aimed to quantify the contribution of root‐respired CO2 to both soil CO2 efflux and xylem CO2 transport by manipulating the autotrophic component of belowground respiration. We compared soil CO2 efflux and the flux of root‐respired CO2 transported in the transpiration stream in girdled and nongirdled 9‐yr‐old oak trees (Quercus robur) to assess the impact of a change in the autotrophic component of belowground respiration on both CO2 fluxes. Stem girdling decreased xylem CO2 concentration, indicating that belowground respiration contributes to the aboveground transport of internal CO2. Girdling also decreased soil CO2 efflux. These results confirmed that root respiration contributes to xylem CO2 transport and that failure to account for this flux results in inaccurate estimates of belowground respiration when efflux‐based methods are used. This research adds to the growing body of evidence that efflux‐based measurements of belowground respiration underestimate autotrophic contributions.